Surgical management of uterine fibroids at Aminu Kano Teaching Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Uterine fibroid is one of the most common pelvic tumours of the female genital tract. Surgery offers long-term relief of symptoms but is associated with complications, hence, the aversion for it in our environment. Therefore, understanding the factors associated with the complications will help to reduce morbidity and mortality.Objective:To determine the surgical options, socio-demographic characteristics, clinical presentations and post-operative complications associated with uterine fibroids at Aminu Kano Teaching Hospital, Kano.Methods:A retrospective review of case notes of 132 surgically managed cases of uterine fibroids at Aminu Kano Teaching Hospital over the study period.Results:Surgical operations for uterine fibroids constituted 21.4% of all gynaecological operations. Most of the cases were seen in 30–39 age group (41.5%) and 51.2% of them were nulliparous. Menorrhagia (53.7%), infertility (26.3%) and abdominal swelling (40.4%) were the common presenting symptoms. Myomectomy was performed in 75.6% of the cases while abdominal hysterectomy accounted for 24.6% of cases. Anaemia was the most common post-operative complication seen in this study (31.7%).Conclusion:Uterine fibroid is common in our environment. The main-stay of management of uterine fibroid is surgery which is associated with post-operative complications. The surgical options used in the management of uterine fibroids in this study were hysterectomy and myomectomy due to lack of requisite skills for the more technical procedures. Improvements in surgical skill will help reduce the frequency and severity of the complications.